2017
DOI: 10.1007/s00253-017-8100-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation on a hexane-degrading strain with different cell surface hydrophobicities mediated by starch and chitosan

Abstract: Bioremediation usually exhibits low removal efficiency toward hexane because of poor water solubility, which limits the mass transfer rate between the substrate and microorganism. This work aimed to enhance the hexane degradation rate by increasing cell surface hydrophobicity (CSH) of the degrader, Pseudomonas mendocina NX-1. The CSH of P. mendocina NX-1 was manipulated by treatment with starch and chitosan solution of varied concentrations, reaching a maximum hydrophobicity of 52%. The biodegradation of hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… Chen et al (2017) discovered that a higher negative zeta potential of of EPS is more beneficial for generating migration potential and increasing the probability of collision between the pollutant molecules and degrading strains. The analysis results show that the zeta potential of the biofilm EPS in the B-BF changed from −13.7 mV to −9.5 mV.…”
Section: Resultsmentioning
confidence: 99%
“… Chen et al (2017) discovered that a higher negative zeta potential of of EPS is more beneficial for generating migration potential and increasing the probability of collision between the pollutant molecules and degrading strains. The analysis results show that the zeta potential of the biofilm EPS in the B-BF changed from −13.7 mV to −9.5 mV.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the EPS had little effect on the adsorption of SCCPs by E. coli strain 2, and it was hypothesized that the lipids absorbed most of the SCCPs [56]. Previous observations have revealed that the surface hydrophobicity of bacteria is closely related to the content of surface lipopolysaccharides in the outer bacterial cell walls [57].…”
Section: Cell Surface Hydrophobicity Analysismentioning
confidence: 97%